Determination of the Chemical Composition of the Extract of Apricot Pomace (Prunus armeniaca L.) - Vorobyova, Victoria; Shakun, Anastasiia; Chygyrynets’, Olena; Skiba, Margarita (Видавництво Львівської політехніки, 2019)
Вивчено комплексну характеристику компо- нентних профілів екстракту абрикосового жмиха (Prunus armeniaca L.) залежно від використовуваних систем розчин- ників. За допомогою ІЧ-спектроскопії, УФ-спектроскопії та газової хромато-мас-спектроскопії проаналізовані екстракти, отримані пропан-2-олом, декаметилциклопентасилоксаном та сумішшю силікону і пропан-2-олу абрикосовогожмиха.

The objective of this study was to investigate a comprehensive characterization of composition profiles of the apricot pomace extract (Prunus armeniaca L) depending on the used solvent systems. The propan-2-ol, decamethylcyclopentasiloxane and the mixture of the apricot pomace extracts are characterized by IR, UVvisible spectroscopy and gas chromatography-mass spectrometry (GС-MS) techniques.
Визначення хімічного складу екстракту абрикосового жмиха (Prunus armeniaca L.)
Keywords: абрикосовий жмих; екстракт; пропан-2-ол; декаметилциклопентасилоксан; альдегіди; терпенові спирти; apricot pomace; extract; propan-2-ol; decamethylcyclopentasiloxane; aldehydes; terpene alcohols